Reduction of Experimental Myocardial Infarct Size by Corticosteroid Administration - Libby, Peter (1973)
The influence of the administration of pharmacologic doses of hydrocortisone on the extent and severity of acute myocardial ischemic injury and on subsequent necrosis after acute coronary occlusion was investigated in 28 dogs. In order to study acute myocardial injury, repeated epicardial electrocardiograms were recorded from 10 to 15 sites on the anterior surface of the left ventricle. Average ST segment elevation (S̄T̄) and the number of sites in which ST segment elevation exceeded 2 mV (NST), indices of the magnitude and extent of myocardial injury, respectively, were analyzed at 30 and 60 min after coronary occlusion. In the control group S̄T̄ and NST did not change significantly in this time interval while in the treated group, which received 50 mg/kg hydrocortisone just after the 30 min recording, S̄T̄ fell from 3.5±0.8 to 1.1±0.4 mV (P<0.01) and NST was reduced from 6.7±1.1 to 1.4±0.8 (P<0.01). In order to study the influence of hydrocortisone on necrosis, epicardial ST segment elevation 15 min after coronary occlusion was compared to myocardial creatine phosphokinase activity (CPK) and histologic appearance 24 h later in each site. In a control group (14 dogs) a relationship was established between ST segment elevation at 15 min (in millivolts) and CPK activity (in international units per milligram of protein) 24 h later: log CPK = -0.0611ST + 1.26 (N = 102 specimens, r = -0.79). In the treated groups, hydrocortisone (50 mg/kg i.v.) was given either at 30 min after occlusion (seven dogs) or at 6 h after occlusion (six dogs). Both groups received supplementary doses of hydrocortisone (25 mg/kg) 12 h after occlusion. The two treated groups exhibited less CPK depression than that expected from ST segment elevation at each site, with slopes of the regression lines which were significantly less steep: log CPK = -0.0288ST + 1.26 (N = 48, r = -0.71) and log CPK = -0.0321ST + 1.31 (N = 48, r = -0.76) in the ½ h and 6 h groups, respectively. Histologically, sites with ST segment elevations of less than 2 mV at 15 min after occlusion exhibited normal appearance 24 h later. Sites with ST segment elevations (> 2 mV) in the control group showed histologic changes compatible with early myocardial infarction in 96% of specimens, while this occurred only in 61% and 63% of specimens, respectively, in the treated groups, showing that over one third of the sites were protected from undergoing necrosis due to the intervening hydrocortisone treatment. Thus pharmacological doses of hydrocortisone prevent myocardial cells from progressing to ischemic necrosis even when administration is initiated 6 h after coronary occlusion.